Light speed rotating Black Holes: The special holes - UV, Satya Seshavatharam (International Journal of Advanced Astronomy, 2013)
Astronomers believe that black holes that are as large as a billion solar masses can be found at the centre of most galaxies. Here the fundamental questions to be answered are: If the galactic central black hole mass is 10 billion solar masses and density is less than 1 kg/m3 - with such a small density and large mass, without collapsing -  how it is able to hold a gigantic galaxy? What force makes the black hole stable? Recent observations indicates that, instead of collapsing, galactic central black holes are growing faster and spinning faster than they expected. From this it can be suggested that, in the universe – ‘black hole geometry’ is most important than its mass and density. In this regard, considering the classical force and power limits an attempt is made to understand the black hole geometry, radius, angular velocity and temperature. Thinking in this way finally an attempt is made to fit the present Hubble’s constant and its obtained value is 66.896 (km/sec)/Mpc. It can be compared with the recently recommended value (67.80+/- 0.77) (km/sec)/Mpc.